Hypoglycaemia Awareness Restoration Programme for People with Type 1 Diabetes and Problematic Hypoglycaemia Persisting Despite Optimised Self-care (HARPdoc): protocol for a group randomised controlled trial of a novel intervention addressing cognitions. Issue 6 (16th June 2019) - Amiel, Stephanie A; Choudhary, Pratik; Jacob, Peter; Smith, Emma Lauretta; De Zoysa, Nicole; Gonder-Frederick, Linda; Kendall, Mike; Heller, Simon; Brooks, Augustin; Toschi, Elena; Kariyawasam, Dulmini; Potts, Laura; et al.
Abstract : Introduction: Severe hypoglycaemia (SH), when blood glucose falls too low to support brain function, is the most feared acute complication of insulin therapy for type 1 diabetes mellitus (T1DM). 10% of people with T1DM contribute nearly 70% of all episodes, with impaired awareness of hypoglycaemia (IAH) a major risk factor. People with IAH may be refractory to conventional approaches to reduce SH, with evidence for cognitive barriers to hypoglycaemia avoidance. This paper describes the protocol for the Hypoglycaemia Awareness Restoration Programme for People with Type 1 Diabetes and Problematic Hypoglycaemia Persisting Despite Optimised Self-care (HARPdoc) study, a trial to assess the impact on hypoglycaemia experience of a novel intervention that addresses cognitive barriers to hypoglycaemia avoidance, compared with an existing control intervention, recommended by the National Institute of Health and Care Excellence. Methods and analysis: A randomised parallel two-arm trial of two group therapies: HARPdoc versus Blood Glucose Awareness Training, among 96 adults with T1DM and problematic hypoglycaemia, despite attendance at education with or without technology use, in four centres providing specialist T1DM services. The primary outcome will be the SH rate at 12 and/or 24 months after randomisation to either course. Secondary outcomes include rates of SH requiring parenteral therapy, involving unconsciousness or needing emergency services; hypoglycaemia awareness status, overall diabetes control and quality of life measures. An implementation study to evaluate how the interventions are delivered and how implementation impacts on clinical effectiveness is planned as a parallel study, with its own protocol. Ethics and dissemination: The protocol was approved by the London Dulwich Research Ethics Committee, the Health Research Authority, National Health Service R&D and the Institutional Review Board of the Joslin Diabetes Center in the USA. Study findings will be disseminated to study participants and through peer-reviewed publications and conference presentations, including user groups. Trial registration number: NCY02940873; Pre-results.